2021
DOI: 10.15414/jmbfs.3211
|View full text |Cite
|
Sign up to set email alerts
|

Propolis: Antimicrobial Activity and Chemical Composition Analysis

Abstract: Apitherapy is one of the practices in natural care, based on products of the hive such as: honey, royal jelly, propolis ... etc. Propolis is a resinous product gathered by honey bees from tree buds (Dimov et al., 1991;Amoros et al., 1992). Its main constituents are beeswax, resin and volatile matter. Mostly, the biological activity of propolis is ascribed to these plant-extracted substances. It has been appeared to have pharmacological properties for example antibacterial, antifungal, antiviral, anti-inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
(13 reference statements)
1
0
1
1
Order By: Relevance
“…Mohdaly et al [37] reported that methanolic extract of propolis from Egypt had a nearly MIC value (1.35 mg/ml) and generally lower MBC value (MBC 1.45 mg/ml) against Salmonella enterica when compared to the MIC and MBC values of propolis extracts against S. enteritidis RSKK 171 in our study. Additionally, ethanolic extract of propolis from other regions in Algeria (El Mechrouha and Ouled Driss regions) presented no antibacterial activity against the tested Gram-negative bacteria [38]. Seidel et al [39] reported that propolis ethanolic extract from various countries showed bacteriostatic activity against Gramnegative bacteria, which is different from our results that revealed the bactericidal effect of both propolis extracts and essential oils on Gram-negative bacteria tested.…”
Section: S Sonnei Mu:57contrasting
confidence: 99%
“…Mohdaly et al [37] reported that methanolic extract of propolis from Egypt had a nearly MIC value (1.35 mg/ml) and generally lower MBC value (MBC 1.45 mg/ml) against Salmonella enterica when compared to the MIC and MBC values of propolis extracts against S. enteritidis RSKK 171 in our study. Additionally, ethanolic extract of propolis from other regions in Algeria (El Mechrouha and Ouled Driss regions) presented no antibacterial activity against the tested Gram-negative bacteria [38]. Seidel et al [39] reported that propolis ethanolic extract from various countries showed bacteriostatic activity against Gramnegative bacteria, which is different from our results that revealed the bactericidal effect of both propolis extracts and essential oils on Gram-negative bacteria tested.…”
Section: S Sonnei Mu:57contrasting
confidence: 99%
“…Regarding the antimicrobial activity of propolis, this was demonstrated in the study by Barud et al 24 , corroborating the data in the literature [5][6][7][8]32 . In the mentioned study, the activity of green propolis was evaluated in vitro against Staphylococcus aureus, S. aureus (MSRA) and Staphylococcus epidermidis.…”
Section: Discussionsupporting
confidence: 86%
“…Em relação à atividade antimicrobiana da própolis, esta foi demonstrada no estudo de Barud e colaboradores 24 , corroborando os dados da literatura [5][6][7][8]32 Cabe destacar que a ação antimicrobiana dos produtos para tratamento de feridas é também um fator essencial nesse processo, uma vez que as lesões infectadas apresentam um retardo na cicatrização devido ao prolongamento da fase inflamatória, que influencia diretamente na deposição de colágeno para contração e epitelização local 33 .…”
Section: Principais Achadosunclassified